Correction: Milk protein complexation enhances post prandial vitamin D3 absorption in rats. Issue 11 (4th November 2020) - Lindahl, Ida Emilie I.; Danielsen, Marianne; Dalsgaard, Trine K.; Rejnmark, Lars; Bollen, Peter; Bertram, Hanne Christine
Abstract : Correction for 'Milk protein complexation enhances post prandial vitamin D3 absorption in rats' by Ida Emilie I. Lindahl et al., Food Funct., 2020, 11, 4953–4959, DOI: ; 10.1039/D0FO01062F .